Foreign Language Writing and Translation - Wuri Soedjatmiko (TEFLIN Journal: A publication on the teaching and learning of English, 2002)
Abstract: In LI writing, every writer is said to have experienced writers block. To overcome this writers are suggested that they continue writing without stopping to edit typing mistakes or find appropriate words. Using 14 fourth-semester students of the English Department whose LI is Indonesian as subjects, and consulting experts findings and experience in writing, this study attempts to qualitatively describe the flow of thoughts of the subjects while writing in English, i.e., whether or not they think in bahasa Indonesia and translate it into English. Three steps are employed. The first is by evaluating the subjects first writing draft to see whether or not they choose appropriate words, compose sentences, and put them in coherent paragraphs. Some guiding assumptions are drawn from their work on the strategies utilized to overcome writers block. The second step is checking through open interviews. The last step sees whether or not the strategies are related to the writers language competence as shown by the average of subjects grades in dictation, reading, writing and structure from Semester 1 to Semester 4. The findings show that strategies used whether or not translation is used are not affected by the subjects language competence. Almost all subjects think in bahasa Indonesia and translate their thoughts into English. From the four subjects who claim to always write directly in English, only two write clearly and well-organized writing, and one of them the best of all even says that she does not hesitate to consult dictionary if necessary. This study then suggests the teaching of EFL writing in class encourage students to think in Indonesian. In writing the first draft, students should be allowed or advised to write the Indonesian expressions to maintain the flow of their writing.